Pengaruh Penggunaan Media Pembelajaran Berupa Alat Peraga Montessori Terhadap Kemampuan Pemecahan Masalah Matematika - Jvana Wahyu Pratami; Arif Rahman Hakim (Universitas Maritim AMNI Semarang, 2024)
This research aims to determine the effect of Montessori learning media on mathematical problemsolving abilities. This research method is experimental with regression analysis techniques. The research sample consisted of 70 Bina Bangsa Vocational School students in South Tangerang City who were taken using a simple random sampling technique. The instrument for measuring mathematical problem solving uses a descriptive test of 5 questions. The results of the research show that there is a significant positive influence of Montessori learning media on mathematical problemsolving abilities with a value of tcount (3.61889) > ttable (3.13167).